Virtual Uprisings: On the Interaction of New Social Media, Traditional Media Coverage and Urban Space during the 'Arab Spring'. (August 2015) - AlSayyad, Nezar; Guvenc, Muna
This article analyses the geography of urban uprising during the so-called Arab Spring, with a focus on the relationship between its virtual and physical dimensions. To enhance understanding of contemporary social movements, it pays particular attention to the interwoven relationship between the social media that now organise gatherings and communicate political messages, the practices of protest in urban space and the magnifying power of global and national media. Using case studies from Tunisia, Egypt and Yemen, it analyses the spatial and temporal aspects of recent protests and suggests that the reciprocal interaction between social media, urban space and traditional media does not simply reproduce relations between these actors, but also transforms them incrementally.